2018
DOI: 10.24926/jrmc.v1i3.1136
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Medical Students and Graduates from Hometown to Practice using Geographic Information Systems, 2011-2017

Abstract: Background: Indiana University School of Medicine (IUSM) through its statewide system provides medical education and clinical experiences across Indiana for more than 1450 medical students in nine regions, including Indianapolis and eight regional medical campuses (RMCs). The majority of medical students begin their education distributed among the RMCs, and some students continue clinical experiences at the RMCs for their third and fourth years. Methods: We used a Geographic Information System (GIS) to visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A more recent study of IUSM graduates from the classes of 2011 to 2017 found that RMC students entered primary care fields in about the same proportions as Indianapolis students, suggesting that the training environments of the RMCs and Indianapolis are sufficiently alike to engender similar career paths for the students. 3 The one exception is the Terre Haute RMC, which produces proportionally more family physicians than any other IUSM campus, but that is largely due to its special Rural Medical Education Program, which emphasizes primary care. 3 Nevertheless, it remains fair to say that students attending the RMCs are probably exposed to more primary care medicine than students attending the Indianapolis campus, which is an academic medical center emphasizing specialty care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study of IUSM graduates from the classes of 2011 to 2017 found that RMC students entered primary care fields in about the same proportions as Indianapolis students, suggesting that the training environments of the RMCs and Indianapolis are sufficiently alike to engender similar career paths for the students. 3 The one exception is the Terre Haute RMC, which produces proportionally more family physicians than any other IUSM campus, but that is largely due to its special Rural Medical Education Program, which emphasizes primary care. 3 Nevertheless, it remains fair to say that students attending the RMCs are probably exposed to more primary care medicine than students attending the Indianapolis campus, which is an academic medical center emphasizing specialty care.…”
Section: Discussionmentioning
confidence: 99%
“…3 The one exception is the Terre Haute RMC, which produces proportionally more family physicians than any other IUSM campus, but that is largely due to its special Rural Medical Education Program, which emphasizes primary care. 3 Nevertheless, it remains fair to say that students attending the RMCs are probably exposed to more primary care medicine than students attending the Indianapolis campus, which is an academic medical center emphasizing specialty care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of integration into local communities to improve outcomes has been clearly identified. [24][25][26] This is particularly important in addressing the needs of rural and remote communities. Similar issues have…”
Section: Strategic Planningmentioning
confidence: 99%
“…Other programs utilize student site preference at the time of admission to make campus assignments. 26 A secondary application for students already accepted to the main campus offers a more manageable and creative campus selection process for a defined and usually limited number of students to attend the RMC. The final campus assignment may be based on both student preference and space availability.…”
Section: Admissionsmentioning
confidence: 99%